STATE HOUSING AND CAUSES DEFORMATION OF BUILDINGS IN THE CITY OF NOVOSIBIRSK - V. S. Vorob’ev; A. S. Sinicyna (Вестник СибАДИ)
The analysis of the existing housing stock of various construction periods and the degree of wear of structural elements of buildings is given. It is noted that in Novosibirsk, a significant increase in housing stock began in 1921. There is a gradual decrease in the total area in the houses of the old building. The number of buildings, whose wear exceeds 65, is increasing. The number of emergency houses and houses requiring major overhaul or reconstruction is growing. The article discusses the feasibility of creating a cadastre of buildings by types of defects for planning the extension of the life cycle when they are eliminated. The main failures of the foundations and foundations, caused by the influence of the human factor, leading to deformation of buildings, are revealed. These include: - poor engineering and geological surveys; - errors in the design of foundations and foundations; - non-qualitative execution of works during erection of the zero cycle; - violation of operation technology. Detailed errors are revealed that lead to deformation of buildings.